Ottoman Mosque in the Balkans as the Legacy for the Contemporary Expression - Jahic, Edin (Journal of History Culture and Art Research, 2018)
The paper explains main characteristics of existing Ottoman monuments in several Balkan countries. Ottoman architectural activity in the Balkan provinces largely reflected architectural styles founded in the principal centers of the Ottoman Empire. A few buildings were designed by the principal architects of the Empire. Traces of local diversity can be found in the designs together with certain variations in building typology, which reflect prevailing social and environmental conditions as well as local traditions, building technique and materials. Among the remaining monuments of urban environments, besides bridges, hans, hammams, and other building types, mosques largely witness a long and rich architectural Ottoman past. Concerning the typology of a mosque, mostly a single–domed type with a three–bay portico and slender minaret was the common model throughout the Balkans from the 16th to 18th century. Today this model still remains in the eyes of many Muslim communities and individuals the ideal model of an Islamic place of worship. The twentieth century, however, has revealed a divergence in approach to the mosque design. While numerous mosques in some Balkan countries are designed on the populist vision of the Ottoman model, a growing number of architects seek to develop a contemporary idiom in mosque design as an appropriate expression of Muslim societies.